Emotional intelligence 2.0 - Bradberry, Travis; Greaves, Jean. (San Diego, Calif. : TalentSmart, 2009)
"Knowing what emotional intelligence is, and knowing how to use it to improve your life, are two very different things." --Publisher
Includes bibliographical references.
Keywords: Self-awareness strategies; Self- management strategies; Social awareness strategies